Anatomy and physiology : - Gunstream, Stanley E. (McGraw Hill, 2006)
Designed for an introductory, one-semester course, the scope, organization, writing style, depth of presentation, and pedagogical aspects of this text have been tailored to meet the needs of students preparing for a career in allied health. This text does not assume any prior science knowledge on the part of the student and effectively presents students with the fundamentals of anatomy and physiology. It's the only one-semester text available with a built-in study guide/workbook.